Prevention of salivary gland dysfunction in patients treated with radioiodine for differentiated thyroid cancer: A systematic review of randomized controlled trials - Auttara-atthakorn, Arunrat; Sungmala, Jaruwan; Anothaisintawee, Thunyarat; Reutrakul, Sirimon; Sriphrapradang, Chutintorn (Frontiers in Endocrinology, 2022)
Introduction: Salivary gland dysfunction (e.g., sialadenitis and xerostomia) is the most common complication of radioactive iodine (RAI) therapy for differentiated thyroid cancer (DTC). Several methods have been used to reduce/prevent this adverse effect. We aimed to systematically review the effectiveness of non-pharmacological and pharmacological interventions in preventing RAI-induced salivary gland dysfunction in patients with DTC. Methods: A systematic review was conducted, according to PRISMA guidelines. The protocol was registered (PROSPERO: CRD42022295229). PubMed, Embase, Scopus, and the Cochrane Library electronic databases were searched from inception to November 2021. Inclusion criteria were randomized controlled trials of DTC patients who were older than 18 years and underwent RAI after thyroidectomy in which at least one studied group received an intervention to prevent salivary gland dysfunction. Results: Twelve studies (a total of 667 participants) were included. Among DTC patients who were treated with RAI, nonpharmacological treatment such as parotid gland massage and aromatherapy ameliorated salivary gland dysfunction. Antioxidants such as vitamin E and selenium demonstrated radioprotective effects on the salivary gland, while other antioxidants did not show radioprotective benefits. Vitamin C showed no significant effects on preventing salivary gland dysfunction. Amifostine had inconsistent outcomes among studies. Among cholinergic agonists, pilocarpine did not demonstrate the radioprotective effect on parotid glands, while bethanechol lowered salivary gland dysfunction. However, the negative results from pilocarpine may be explained by the strong sialorrheic effect of the Cincinnati regimen in both study arms. Conclusion: Among non-pharmacological and pharmacological methods, parotid gland massage, aromatherapy, vitamin E, selenium, amifostine, and bethanechol may have benefits in minimizing RAI-induced salivary gland dysfunction in patients with DTC. The results are limited by a small number of patients and should be confirmed in future larger randomized controlled trials.